Dynamics Analysis of a Viral Infection Model with a General Standard Incidence Rate. (14th October 2014) - Ji, Yu; Zheng, Muxuan
Abstract : The basic viral infection models, proposed by Nowak et al. and Perelson et al., respectively, have been widely used to describe viral infection such as HBV and HIV infection. However, the basic reproduction numbers of the two models are proportional to the number of total cells of the host's organ prior to the infection, which seems not to be reasonable. In this paper, we formulate an amended model with a general standard incidence rate. The basic reproduction number of the amended model is independent of total cells of the host's organ. When the basic reproduction numberR 0 < 1, the infection-free equilibrium is globally asymptotically stable and the virus is cleared. Moreover, ifR 0 > 1, then the endemic equilibrium is globally asymptotically stable and the virus persists in the host.